Can downwelling far-infrared radiances over Antarctica be estimated from mid-infrared information? - Bellisario, C; Brindley, HE; Tett, SFB; Rizzi, R; Di Natale, G; Palchetti, L; Bianchini, G (Copernicus Publications, 2018)
Far-infrared (FIR: 100 cm−1 < wavenumber, ν < 667 cm−1) radiation emitted by the Earth and its atmosphere plays a key role in the Earth's energy budget. However, because of a lack of spectrally resolved measurements, radiation schemes in climate models suffer from a lack of constraint across this spectral range. Exploiting a method developed to estimate upwelling far-infrared radiation from mid-infrared (MIR: 667 cm−1 < ν < 1400 cm−1) observations, we explore the possibility of inferring zenith FIR downwelling radiances in zenith-looking observation geometry, focusing on clear-sky conditions in Antarctica. The methodology selects a MIR predictor wavenumber for each FIR wavenumber based on the maximum correlation seen between the different spectral ranges. Observations from the REFIR-PAD instrument (Radiation Explorer in the Far Infrared – Prototype for Application and Development) and high resolution radiance simulations generated from co-located radio soundings are used to develop and assess the method. We highlight the impact of noise on the correlation between MIR and FIR radiances by comparing the observational and theoretical cases. Using the observed values in isolation, between 150 and 360 cm−1, differences between the true and extended radiances are less than 5 %. However, in spectral bands of low signal, between 360 and 667 cm−1, the impact of instrument noise is strong and increases the differences seen. When the extension of the observed spectra is performed using regression coefficients based on noise-free radiative-transfer simulations the results show strong biases, exceeding 100 % where the signal is low. These biases are reduced to just a few percent if the noise in the observations is accounted for the simulation procedure. Our results imply that while it is feasible to use this type of approach to extend mid infrared spectral measurements to the far-infrared, the quality of the extension will be strongly dependent on the noise characteristics of the observations. A good knowledge of ...